Raport. Pierwsza fala pandemii COVID-19 w Polsce: Ograniczenia i pomoc kierowana do przedsiębiorców - Koman, Kacper; Syta, Ziemowit (Wydawnictwo Księgarnia Akademicka, 2022)
REPORT. THE FIRST WAVE OF THE COVID-19 PANDEMIC IN POLAND: RESTRICTIONS AND AID ADDRESSED TO ENTREPRENEURS The report presents a review of legal norms and a questionnaire study of the first wave of the COVID-19 pandemic in Poland (March to June 2020). The authors analysed legal regulations for four business industries: catering, tourism, transportation, and construction, both in terms of laws restricting the operation of these businesses due to the pandemic and aid regulations. The main objective of the research was to check whether the constitutionally established mechanism of determining the addressee’s relevant feature in formulating the aid solutions remains valid in the case of aid provided by the state to entrepreneurs affected by the pandemic crisis. The publication also contains observations and analyses concerning historical crises caused by forces of nature that occurred in Poland when the current Constitution was in force, and the methods of fighting the resulting damage at that time, with particular emphasis on the legal mechanisms that were applied in these situations. The summary of the report contains postulates of de lege ferenda character, whose introduction to the Polish legal order would result in a much higher than now level of preparedness of the state authorities for systemic, organised assistance in predefined forms to entities affected by natural disasters, with particular consideration of possible future events bearing traits of a pandemic.